Tokoh dan Penokohan serta Nilai Moral dalam Cerita Fabel - Riska Dewi Saputri; Herlina Setyowati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to determine (1) characters and characterizations; and (2) moral values ​​in fable stories. This study is a qualitative descriptive study. The source of data in this study is a story entitled "Piwulang kanggo Cempe," "Anak Gajahlan Semut Ireng," and "Kancil kang Cerdik" contained in Djaka Lodang magazine. The research data collection techniques used were library techniques and note-taking techniques. The instrument used is the research itself. The data analysis technique uses qualitative analysis methods. The results showed: (1) the characters in the fable of "Piwulang Kanggo Cempe" are Babon Domba dan Anak Domba or Cempe, in the fable story “Anak Gajah Lan Semut Ireng” are Anak Gajah and Semut Ireng, and in the fable story "Kancil Kang Cerdik" is Kancil, Manuk Blekok, and Manuk Bangau. The characterizations are shown analytically and dramatically. Furthermore, the moral values ​​contained in the three fables are about obedience to parents, helping others, respecting others, being honest, and establishing friendships.